Validity of interactive learning media in computer basics course - Pratama, Muh. Putra; Ruruk, Simon; Karuru, Perdy (Jurnal Inovasi Teknologi Pendidikan, 2023)
This study aims to determine the validity and practicality of interactive media in computer basics courses in the educational technology study program at Universitas Kristen Indonesia Toraja. This type of development research uses the ADDIE research model (Analysis, Design, Development, Implementation, and Evaluation). The results of the validity and practicality tests can be used as a reference for assessing the media that has been developed. This research has conducted a content validity test; the quality of interactive media based on the assessment by teaching material expert lecturers shows an average of 3.77 from a maximum average score of 4.00. Thus, interactive media shows criteria worth using. The results of the media validity test that the quality of interactive media based on the assessment by media expert lecturers shows an average of 3.58 from a maximum average score of 4.00; thus, the module indicates very feasible criteria. The interactive media practicality test results showed that the interactive media developed an average of 3.46 from an average score of 4.00. Thus, the module showed efficient criteria.